Chemical Reactor Design for Hydrogen Generation from Solid Sodium Borohydride by Ferric(III) Sulfate - Yan, Chang-Feng; Fang, Zhaojun; Huang, Shilin; Guo, Changqing; Hu, Rongrong; Luo, Weimin (Asian Journal of Chemistry, 2015)
Catalytic generation of hydrogen from the hydrolysis of sodium borohydride over ferric(III) sulfate has been studied in a new reactor. The system NaBH4- ferric(III) sulfate (both in solid state) is an attractive storage way for portable application. 1) ferric(III) sulfate was cost-effective, 2) the solid state of NaBH4 do not need the stabilizer regent, 3) A toroidal tube distributor helps to disperse water uniformly in order to constant generation of hydrogen and 4) no pretreatment step was needed. The effects of catalyst to sodium borohydride ratio, water flow rate and initial temperature on hydrogen generation were investigated. Hydrogen yield of > 90 % can be achieved with pure water and an active non-noble intermediate, Fe2B, produced during the reaction. A burst of hydrogen flow rate accompanied with the appearance of the highest reaction temperature caused by exothermic effect. The rate of hydrolysis reaction was sensitive to temperature.